Malnutrition in Elderly Population: Screening Tools and Management - Tanira, Shaorin; Tanzil, Merina; Alamgir, Sadia Nusrat; Amin, Raihana; Muqueet, Md Abdul; Sazib, SM Farhad (Community Based Medical Journal, 2022)
Malnutrition is a common, potentially serious, and frequently under-diagnosed condition among elderly people. Age-related physiologic changes in combination with organic and psychological disease processes contribute to the development of malnutrition in older adults. Profound malnutrition and serious illnesses often present concurrently, and each can accelerate the progression of the other. Early detection and careful interventions are very important to prevent further deterioration. However, Prompt diagnosis relies on physicians‟ clinical suspicion and available screening tools. We consider that systematic screening and early treatment of malnutrition are integral parts of global geriatric care. Hence, this paper aims to review the prevalence and aetiology of malnutrition among ageing population with a special focus on some of the commonly used screening tools in clinical practice. Some of the non-pharmacologic and pharmacologic interventions are also highlighted that are used to manage malnutrition in elderly patients. CBMJ 2022 January: vol. 11 no. 01 P: 61-68